The Efficacy of Adjuvant Corticosteroids in Surgical Management of Chronic Subdural Hematoma: A Systematic Review and Meta-Analysis - Tang, Guoqiang; Chen, Jiabei; Li, Bin; Fang, Song (Frontiers in Neurology, 2022)
Objective: This systematic review aimed to assess the efficacy of adjuvant corticosteroids in managing patients with chronic subdural hematoma (CSDH) undergoing surgical intervention. Methods: We searched for eligible studies electronically on the databases of PubMed, Embase, and Google Scholar. The last date of the search was 15th Jun 2021. Outcomes were pooled to calculate risk ratios (RR) with 95% confidence intervals (CI). Results: Eleven studies were included. Four of them were randomized controlled trials (RCTs). Six studies reported data on good neurological outcomes but with variable definitions. Combining all studies, we noted no statistically significant difference in good neurological outcome with the use of adjuvant corticosteroids (RR: 0.91 95% CI: 0.74, 1.12 I2=92% p=0.39). Similar results were obtained on subgroup analysis based on definition and study type. However, the use of adjuvant corticosteroids was associated with a significantly reduced risk of recurrence (RR: 0.51 95% CI: 0.40, 0.64 I2=0% p<0.0001). The meta-analysis also demonstrated no statistically significant difference in mortality rates with the use of adjuvant corticosteroids (RR: 1.01 95% CI: 0.47, 2.21 I2=76% p=0.97). The results did not differ between RCTs and non-RCTs. Limited studies reported data on complications, and pooled analysis indicated no significant increase in infectious, gastrointestinal, and neurological complications with the use of adjuvant corticosteroids. Conclusion: The use of corticosteroids with surgery for CSDH might be associated with a reduction in recurrence rate. However, corticosteroids do not improve functional outcomes or mortality rates. Future studies should assess the impact of different corticosteroid regimens on patient outcomes, and should use standardized reporting of neurological outcomes with uniform follow-up duration.